2018
DOI: 10.1016/j.coal.2018.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Permeability changes in coal seams: The role of anisotropy

Abstract: The permeability of coal seams is pore pressure-dependent. A number of analytical models have been proposed to investigate this problem, but many disregard a crucial factor: the anisotropy of coal. This paper is devoted to investigating the role of anisotropy in modeling the change of horizontal permeability with pressure. Analysis is conducted using a fully anisotropic model that incorporates both the anisotropies of mechanical properties and of the permeability dependence on stresses. Analytical expressions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The limitation of the existing isotropic permeability model, which is commonly adopted in numerical simulation, results in this failure. Actually, coal is one kind of typically anisotropic material, including permeability and mechanical properties, particularly in the cases of low-rank coal seams [41,42]. Figure 16 shows that the aperture sizes of the cleats (face and butt cleats) and structure of bedding planes, which potentially cause the permeability anisotropy.…”
Section: Discussionmentioning
confidence: 99%
“…The limitation of the existing isotropic permeability model, which is commonly adopted in numerical simulation, results in this failure. Actually, coal is one kind of typically anisotropic material, including permeability and mechanical properties, particularly in the cases of low-rank coal seams [41,42]. Figure 16 shows that the aperture sizes of the cleats (face and butt cleats) and structure of bedding planes, which potentially cause the permeability anisotropy.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between coal permeability and pressure sensitivity was studied using coal samples collected from the Xinyuan coal mine in Yangquan city. The study showed the following: (1) permeability of coal exhibits anisotropy, (2) permeability along the strike of the coal seam is higher than that along the direction of propensity (Wang et al 2018). These observations indicate that coal permeability is highly sensitive to stress anisotropy.…”
Section: Introductionmentioning
confidence: 99%
“…Gas adsorption/desorption causes a surface energy change, which leads to coal matrix and bulk rock swelling/shrinkage . The magnitudes of swelling/shrinkage in different directions can be substantially different (anisotropic swelling/shrinkage). When gas flows through coal, gas pressure variation (effective stress variation) changes the fracture (cleat) aperture, resulting in permeability evolution. , Meanwhile, gas adsorption/desorption induces swelling/shrinkage of coal matrices near the fracture (cleat) surface (internal surface), which narrows/opens the fractures (cleats) and reduces/increases coal permeability. This swelling/shrinkage phenomenon is called internal swelling/shrinkage and is regarded as a key factor affecting coal permeability evolution. , In addition, the impact of the gas rarefaction phenomenon (gas slippage) on permeability has been widely observed in different experiments. For the small flow channels within coal, the permeability is also influenced by gas rarefaction effects, ,,, which lead to invalid classical permeability effective stress laws . Due to the aforementioned factors, it is challenging to accurately describe the anisotropic coal permeability evolution in the process of gas injection/extraction under the combined effects of effective stress, anisotropic internal swelling/shrinkage, and the gas rarefaction phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…6−8 When gas flows through coal, gas pressure variation (effective stress variation) changes the fracture (cleat) aperture, resulting in permeability evolution. 9,10 Meanwhile, gas adsorption/desorption induces swelling/shrinkage of coal matrices near the fracture (cleat) surface (internal surface), which narrows/opens the fractures (cleats) and reduces/increases coal permeability. 9−11 This swelling/shrinkage phenomenon is called internal swelling/ shrinkage and is regarded as a key factor affecting coal permeability evolution.…”
Section: Introductionmentioning
confidence: 99%